Collaborative Analysis of the Bengkulu City Regional Government in Overcoming Waste at the Tourism Object - Nusantara, Bella Dian; Yuwono, Teguh; Yuniningsih, Tri (Universitas Muhammadiyah Ponorogo, 2022)
The efforts of the Bengkulu City Regional Government in dealing with waste have been quite good by issuing various regional regulations and mayoral regulations, but in the field trash still piles up here and there, this is the background to the research because waste is not managed properly at the Jakat beach tourism object. This study aims to analyze how the collaboration of the Bengkulu city government in dealing with waste in tourism objects. This research method was carried out using a qualitative approach with case studies that focused on what kind of collaboration the Bengkulu city government had in dealing with waste at the Jakat Beach tourism object. Data was collected through in-depth interviews and discussions with the Bengkulu City Regional Government's State Civil Apparatus (ASN), micro-entrepreneurs who are active in the Jakat Beach tourism object. There were 6 informants who came from 3 stakeholders, namely micro entrepreneurs, communities and local government. The results of the study show that the collaboration carried out by the Bengkulu City Government in dealing with waste has not been optimal, it has been confirmed that the Bengkulu City Regional Government does not yet have a legal/written collaboration with any party to deal with waste at the Jakat Beach tourist attraction